Landscape Connectivity Limits the Predicted Impact of Fungal Pathogen Invasion - Li, Zhimin (J Fungi (Basel), 2020)
Infectious diseases are major drivers of biodiversity loss. The risk of fungal diseases to the survival of threatened animals in nature is determined by a complex interplay between host, pathogen and environment. We here predict the risk of invasion of populations of threatened Mediterranean salamanders of the genus Lyciasalamandra by the pathogenic chytrid fungus Batrachochytrium salamandrivorans by combining field sampling and lab trials. In 494 samples across all seven species of Lyciasalamandra, B. salamandrivorans was found to be absent. Single exposure to a low (1000) number of fungal zoospores resulted in fast buildup of lethal infections in three L. helverseni. Thermal preference of the salamanders was well within the thermal envelope of the pathogen and body temperatures never exceeded the fungus’ thermal critical maximum, limiting the salamanders’ defense opportunities. The relatively low thermal host preference largely invalidates macroclimatic based habitat suitability predictions and, combined with current pathogen absence and high host densities, suggests a high probability of local salamander population declines upon invasion by B. salamandrivorans. However, the unfavorable landscape that shaped intraspecific host genetic diversity, lack of known alternative hosts and rapid host mortality after infection present barriers to further, natural pathogen dispersal between populations and thus species extinction. The risk of anthropogenic spread stresses the importance of biosecurity in amphibian habitats.